Charge and phonon transport in PbTe-based thermoelectric materials. Issue 1 (December 2018) - Xiao, Yu; Zhao, Li-Dong
Abstract PbTe is a typical intermediate-temperature thermoelectric material, which has undergone extensive developments and achieved excellent high thermoelectric performance. In this perspective we summarized several strategies that were successfully applied in PbTe-based thermoelectric materials through manipulating charge and phonon transports, such as optimizing carrier density to tune Fermi level, tailoring band structure to enhance effective mass, and designing all-scale hierarchical architectures to suppress phonon propagation. Meanwhile, due to the different features of conduction and valence bands, we separately introduced the approaches to enhance performance of p-type and n-type PbTe. In p-type PbTe, the strategies of band convergence, band alignment and density of state (DOS) distortion are more effective to achieve high electrical transport properties. By contrast, flattening conduction bands and introducing deep impurity level are more suitable for n-type PbTe. Lastly, several potential strategies were proposed to further improve the thermoelectric performance of PbTe-based materials, which might be extended to other thermoelectric systems.